Behavioral and sensitivity responses of pomacea insularum to Cd and Cu toxicities - Yap, Chee Kong; Pang, Bin Huan; Cheng, Wan Hee; Omar, Hishamuddin (Nova Science Publishers, 2017)
This chapter focuses on the toxicity test of Cd and Cu by using two different sized groups of Pomacea insularum as a test organism, with mortality as an endpoint. The findings indicate the mussel was more sensitive to Cu than Cd although the small size group was more sensitive than the large one since the small group had lower LC50 values than the large one. Results also indicated the ability of P. insularum as a potential bioindicator for acute and subacute exposures to Cu and Cd. This study has provides an important baseline information for Cd and Cu toxicities using P. insularum as a test organism which enables the comparison of the acute sensitivity of P. insularum towards Cd and Cu with other marine invertebrates.